2022
DOI: 10.1136/bmjopen-2021-056017
|View full text |Cite
|
Sign up to set email alerts
|

Time-series cohort study to forecast emergency department visits in the city of Milan and predict high demand: a 2-day warning system

Abstract: ObjectivesThe emergency department (ED) is one of the most critical areas in any hospital. Recently, many countries have seen a rise in the number of ED visits, with an increase in length of stay and a detrimental effect on quality of care. Being able to forecast future demands would be a valuable support for hospitals to prevent high demand, particularly in a system with limited resources where use of ED services for non-urgent visits is an important issue.DesignTime-series cohort study.SettingWe collected al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Wargon et al [ 42 ] showed that the day of the week has a powerful influence in modelling the number of patients reporting at EDs, but adding meteorological data to the model did not increase its sensitivity, which finally gave indications with an error of the number of patients reporting at the level of 4.2% to 14.4%. Additionally, the conclusions contained in the paper by Murtas et al [ 43 ], regarding the number of visits to EDs depending on the day of the week, coincided with the previously described studies. The most frequent reports were on weekends for children and Mondays for adults and seniors.…”
Section: Discussionsupporting
confidence: 77%
“…Wargon et al [ 42 ] showed that the day of the week has a powerful influence in modelling the number of patients reporting at EDs, but adding meteorological data to the model did not increase its sensitivity, which finally gave indications with an error of the number of patients reporting at the level of 4.2% to 14.4%. Additionally, the conclusions contained in the paper by Murtas et al [ 43 ], regarding the number of visits to EDs depending on the day of the week, coincided with the previously described studies. The most frequent reports were on weekends for children and Mondays for adults and seniors.…”
Section: Discussionsupporting
confidence: 77%